The Influence of Local Tax Services and Taxpayer Awareness on Local Revenue Increase in Sukoharjo Regency Revenue Management Agency - Ramadhani, Annas Rahmat; Nurrahmah, Yan Yashinta; Gamat, Mutia Taqina; Nadeak, Putry H.; Nurdin, Ade Ali; Darulmalshah , Destian Arshad (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The local tax service system at the Financial Management, Revenue and Regional Assets Agency of Sukoharjo Regency is carried out face-to-face by taxpayers who come directly to the office. The transition to a new website-based local tax service system makes it easier for taxpayers to fulfil their tax obligations. The emergence of this convenient service can improve taxpayer awareness, which can affect the original local government revenue. The ultimate goal of this research is to analyse the impact of the local tax service system and the taxpayer's awareness level on increasing the original local government revenue at the Financial Management, Revenue and Regional Assets Agency of Sukoharjo Regency. In fulfilling these objectives, the author uses a quantitative method, while the research samples are taken from local taxpayers who have registered at the Financial Management, Revenue and Regional Assets Agency of Sukoharjo Regency. The author collects data by distributing questionnaires and conducting a documentation study, while the data analysis techniques use multiple linear regression on classic assumption tests and hypothesis tests. The results show that there is a simultaneous and partial influence through the correlation of the Regional Tax Service System and the Regional Taxpayer Awareness Level on increasing Regional Original Revenue in Sukoharjo Regency.